Numerical modeling of explosion of a reinforced concrete magazine : the effect of earth cover - Lin, Yongxiang. (2010)
Numerical simulation of internal explosion in the concrete magazines has advantages over conventional field tests in terms of cost, safety and land availability. Adopting the well established simulation methodologies from the previous studies, this study aimed to further explore the soil cover effect in the box-shape Earth-Covered Magazine (ECM) under different TNT loading densities and different soil plasticity. With the focus on top wall and simplicity, a quarter model design with the two side walls fully constrained was adopted. Reinforcement was not included. Pairs of AGM and ECM (with low soil plasticity) were test under different loading densities, including 0.6kg/m3, 5.5 kg/m3 and 22.5 kg/m3. In addition, this study also included two more ECM cases (one for 5.5 kg/m3 and the other for 22.5 kg/m3) with high soil plasticity. Key parameters including pressure, impulse and resultant velocity were tracked to study the blast effect. Important conclusions drawn from the results were: 1) With low soil plasticity, the earth cover was effective in alleviating the debris launching velocity only under the 5.5 kg/m3 loading density; 2) With high soil plasticity, the earth cover however increased the blast effect and resulted in an even higher velocity in the ECM than the AGM.